Exploring the potential mechanisms of Urban greenspaces providing pollution Retention and cooling benefits based on three-dimensional structure of plant communities - Miao Yu; Xiayuan Mi; Yunyuan Li; Chuling Jiang; Kang Ding; Chang Wang; Linghao Cai (Scientific Reports)
Abstract Establishing urban greenspaces is an effective approach for improving urban air quality and thermal environments. However, at a finer scale, the potential mechanisms of urban greenspaces providing pollution retention and cooling benefits remain unclear, especially for the three-dimensional structural characteristics of plant communities. To explore the potential mechanisms, we conducted field experiments on 108 plant communities in Beijing and simultaneously monitored PM10 concentration data and meteorological data both within and outside the plant communities. We analyzed the relationships between three-dimensional structural characteristic factors, the pollution retention benefit, and the cooling benefit. The results indicated that the majority of the plant communities (90.91%) can simultaneously provide both benefits. The herbaceous layer was a crucial factor influencing the pollution retention benefit, with a nonlinear positive correlation between the pollution retention benefit and the ratio of three-dimensional green biomass of herbs and trees (RTDGB-HT) and a threshold of 0.80-1.00. The tree layer was a crucial factor influencing the cooling benefit, as indicated by a positive linear correlation between the cooling benefit and the ratio of three-dimensional green biomass of trees (RTDGB-T). With changes in three-dimensional structural characteristic factors, the rate of change in pollution retention benefit factors was 3-5.5 times that in cooling benefit factors. Mediation analysis confirmed the trade-off between the pollution retention and cooling benefits, with trees indirectly enhancing pollution retention benefit by reducing the daily mean temperature reduction rate (R-Tmean) by 20.44-22.27% and by reducing the daily maximum temperature reduction rate (R-Tmax) by 13.14-15.99%. Overall, 13–23% of the pollution retention benefit was achieved through reducing cooling benefit, and interventions involving extreme heat can minimize the trade-off between the pollution retention and cooling benefits compared to reducing cooling benefit throughout the day. Our findings enrich and extend the current understanding of the correlations associated with the comprehensive benefits at the plant community scale, emphasizing the differences in three-dimensional structural characteristics that provide different benefits, which can better inform the development of refined and scientifically managed strategies for green space renovation.